2020
DOI: 10.1080/03610470.2020.1843964
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Different Contemporary Barley Genotypes Enhances and Expands the Scope of Barley Contributions to Beer Flavor

Abstract: Recent research has demonstrated contributions of barley genotype to beer flavor based on the progeny of a cross between an heirloom and a more contemporary barley variety. To advance this line of research, the current study used two independent sets of barley germplasm to address the contributions of different barley genotypes to beer flavor. Pedigree, quality of malt and beer, and beer metabolomic profiles were compared within and between the two sets. Utilizing both laboratory and consumer panels, differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…[6] Developing a deeper understanding of the contributions of barley genotype to malt and beer flavor is an area of active research. [7][8][9][10] Previously, research on barley genotype contribution to beer flavor was limited to negative flavor outcomes such as dimethyl sulfide (DMS) and associated precursors [11] or lipoxygenase (LOX) activity. [12,13] Briefly, Herb et al [9] -using sensory evaluation -found that barley genotype and production environment contribute to beer flavor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Developing a deeper understanding of the contributions of barley genotype to malt and beer flavor is an area of active research. [7][8][9][10] Previously, research on barley genotype contribution to beer flavor was limited to negative flavor outcomes such as dimethyl sulfide (DMS) and associated precursors [11] or lipoxygenase (LOX) activity. [12,13] Briefly, Herb et al [9] -using sensory evaluation -found that barley genotype and production environment contribute to beer flavor.…”
Section: Introductionmentioning
confidence: 99%
“…[7,14,15] Bettenhausen et al [8] applied metabolomic profiling, together with beer sensory, to three selections from the same germplasm used by Herb et al [9] -derived from the cross of Golden Promise and Full Pint -that were grown at the same location and malted at the same facility. Windes et al [10] used a novel method for malt sensory analysis (American Society of Brewing Chemists malt hot steep extract method), [16] as well as beer sensory and metabolomics, in order to better trace barley variety contributions to malt and beer flavor in two sets of barley germplasm -one comprised of potential spring habit varieties and the other of contemporary winter malting varieties that did not include Maris Otter. The research described in this report continues using this flavor research pipeline to evaluate the use of an heirloom barley variety as a breeding parent and its impacts on malt and beer flavor and chemical profiles of the resulting progeny.…”
Section: Introductionmentioning
confidence: 99%
“…The Laureate variety scored significantly higher ( p < 0.01) for the floral sensory attribute in 2018 only. Flavour differences between varieties has been previously reported in beer [ 20 , 63 ]. In this study, significant differences between the varieties were evident for only two sensory attributes (pungent and fresh fruit) in 2017 and for four (pungent, fresh fruit, malty/biscuit, and floral) in 2018 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 95%
“…The lack of significance across a higher number of sensory attributes between both Laureate and Olympus varieties suggests that in this study, the impact of variety is of less significance in comparison to environment. This may be a direct result of genetic distance between the two chosen varieties, as Windes et al suggested that genetic distance between barley varieties may be a significant variable in the differential flavour profiling of lager beer and that the variation was greater between genetic linkage groups than within genetic linkage groups [ 63 ]. As Laureate and Olympus varieties were developed within similar genetic backgrounds, both sharing a common ancestor (Quench SB) and originating from European germplasm, these may be less likely to produce different flavour attributes than varieties derived from a wider germplasm [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The beer with the highest overall liking had desirable traits such as refreshing, crisp, citrus, sweet, and light (Bettenhausen et al, 2020). Windes et al (2021) found that a beer made with the variety Violetta had the highest overall liking and was more sweet and floral than a beer made with Calypso, which had the lowest degree of liking. In that study, consumers identified crisp and refreshing as ideal lager traits.…”
Section: Introductionmentioning
confidence: 97%